The effect of high rearing densities on the growth of juveniles of the cichlid, cichlasoma managuense (Günther, 1869) (ESP) - Günther Nonell, Jorge; Gálvez Hidalgo, Nazira (Uniciencia, 1992)
The effect of high density culture on the growth of juvenile jaguar cichlids was investigated. Mean growth rate decrease with density, while the growth rate of the largest fishes was not affected. Reduction in mean growth resulted from a greater number of stunted individuals as well as from a higher degree of stunting. Skewness appears to be a better indicator of competitive effects than the coefficient of variation. It is concluded that at least in stagnant waters, even high densities do not affect the strong dominance hierarchy which establishes among guapote juveniles.